Design of Volume Control Type Portable Mechanical Ventilator - Ishak; Nurhidayanti; Muh. Abdillah; Wicaksono, Ariawan Bayu (Department of Mechanical Engineering, Universitas Andalas, 2025)
This research addresses the critical need for affordable, portable ventilators, particularly for patients with respiratory distress, including those with COVID-19. These devices are essential for initial patient care during transport to hospitals. This project focuses on developing a volume-controlled ventilator that adheres to fundamental medical standards, enabling precise adjustments of tidal volume (VT), I/E ratio, and respiratory rate (RR). The ventilator utilizes an Arduino Mega 2560 controller to manage a solenoid valve, which regulates airflow for inspiration and expiration. Tidal volume, the volume of air delivered per breath, is adjustable between 50ml and 805ml, with selectable increments of 5ml to 20ml. The solenoid valve's activation controls the inspiration phase, allowing for adjustable inspiration times from 0.25 to 3.8 seconds. Conversely, deactivation facilitates expiration, with adjustable expiration times from 0.75 to 6.3 seconds. This precise control over respiratory parameters aims to provide effective and adaptable respiratory support, enhancing accessibility to crucial medical interventions.